PENYELESAIAN KERUGIAN KEUANGAN NEGARA - Henny Juliani (Masalah-Masalah Hukum, 2010)
In order to implement governance and development to realize people prosperity, Government us bestowedauthority to manage public finance. The authority is classified as administrative authority and treasuryauthority. The authority on public finance management belonged to the government gives consequence toaccount on implementation of public finance management. Hence every behavior effecting public financeloss have to be accounted jurisdictionally. Those above mention undergird paper of ULegalAspect of Publicfinance Loss Solution~". Government's behaviors comprise in managing and accounting public finance,comprises the authorities as to manage and to account the public finance management are obtained asattributed and delegated based on legality and discretion. In implementing its authority, there is a risk toabuse the authority as well as illega/ behaviors accordingly they may causes public finance loss. Hence theillegal behaviors causing public finance loss have to be accounted legally.